Altered metabolic landscape in IDH‐mutant gliomas affects phospholipid, energy, and oxidative stress pathways. Issue 12 (20th October 2017) - Fack, Fred; Tardito, Saverio; Hochart, Guillaume; Oudin, Anais; Zheng, Liang; Fritah, Sabrina; Golebiewska, Anna; Nazarov, Petr V; Bernard, Amandine; Hau, Ann‐Christin; Keunen, Olivier; Leenders, William; et al.
Abstract: Heterozygous mutations in NADP‐dependent isocitrate dehydrogenases (IDH) define the large majority of diffuse gliomas and are associated with hypermethylation of DNA and chromatin. The metabolic dysregulations imposed by these mutations, whether dependent or not on the oncometabolite D‐2‐hydroxyglutarate (D2HG), are less well understood. Here, we applied mass spectrometry imaging on intracranial patient‐derived xenografts of IDH‐mutant versus IDH wild‐type glioma to profile the distribution of metabolites at high anatomical resolution in situ . This approach was complemented by in vivo tracing of labeled nutrients followed by liquid chromatography–mass spectrometry (LC‐MS) analysis. Selected metabolites were verified on clinical specimen. Our data identify remarkable differences in the phospholipid composition of gliomas harboring the IDH1 mutation. Moreover, we show that these tumors are characterized by reduced glucose turnover and a lower energy potential, correlating with their reduced aggressivity. Despite these differences, our data also show that D2HG overproduction does not result in a global aberration of the central carbon metabolism, indicating strong adaptive mechanisms at hand. Intriguingly, D2HG shows no quantitatively important glucose‐derived label in IDH‐mutant tumors, which suggests that the synthesis of this oncometabolite may rely on alternative carbon sources. Despite a reduction in NADPH, glutathione levels are maintained. We found that genes coding for key enzymes in de novo glutathione synthesis are highly expressed in IDH‐mutant gliomas and the expression of cystathionine‐β‐synthase ( CBS ) correlates with patient survival in the oligodendroglial subtype. This study provides a detailed and clinically relevant insight into the in vivo metabolism of IDH1‐mutant gliomas and points to novel metabolic vulnerabilities in these tumors. Synopsis: Oncogenic isocitrate dehydrogenase (IDH) mutations are a major glioma subtype determinant. Mass spectrometry imaging (MSI) and LC‐MS on patient‐derived orthotopic IDH‐mutated glioma xenografts reveal IDH‐specific adaptive mechanisms in metabolic pathways. Altered phospholipid metabolism is a major abnormality associated with IDH‐mutant gliomas. IDH‐mutant gliomas display a low energy potential as shown by a reduced ATP/ADP ratio. Potential compensatory pathways to maintain glutathione levels and thus redox balance are established. Cystathionine‐β‐synthase (CBS) expression is a novel prognostic factor in the oligodendroglial glioma subtype. Abstract : Oncogenic isocitrate dehydrogenase (IDH) mutations are a major glioma subtype determinant. Mass spectrometry imaging (MSI) and LC‐MS on patient‐derived orthotopic IDH‐mutated glioma xenografts reveal IDH‐specific adaptive mechanisms in metabolic pathways.